The Influence of Tides on Coastal Plain Channel Geomorphology: Altamaha River, Georgia, USA. Issue 7 (19th July 2021) - Sulaiman, Z. A.; Viparelli, E.; Torres, R.; Yankovsky, A.; Grego, J.
Abstract: Rivers that traverse the terrestrial‐marine interface may have lower reaches that are influenced by both terrestrial and marine processes. However, only a handful of studies have focused on how the interactions of fluvial and tidal processes translate to channel geomorphology, and those are largely from delta/distributary systems. Here we quantify channel properties along the fluvial‐tidal transition reach of a coastal plain river and provide insight into their origins. The study site is a 47 km long tidal, single‐thread freshwater section of a river at 29 to 76 river kilometers inland of the estuary mouth, upstream of the delta/distributary system, and with average riverbed slope of 10 −4 . Results show that a tidal wave approaching the study reach loses 15%–17% of its incident energy (per horizontal area) per kilometer of channel, and at 51 km upstream of the mouth the incident energy is reduced to <1%. Also, at or near 51 km we observed breaks in along‐channel trends of channel cross‐section geometry, bed grain size, sinuosity, channel bed and water surface slopes. We propose that fluvial‐tidal flow processes and corresponding geomorphic feedbacks are apparent as abrupt changes in channel properties that highlight the influence of tides, and these discontinuities may be endemic to fluvial‐tidal transition zones in general. How these transition reaches self‐adjust in response to climate change remains largely unexplored but these reaches are likely to become important geomorphic hotspots. Plain Language Summary: Rivers that reach the ocean physically connect terrestrial (or "fluvial") river channels shaped by downstream water flows, and marine river channels, shaped by upstream and downstream flows. Therefore, in coastal environments, the landward river reach can be dominated by fluvial conditions, while oceanward the river can be dominated by marine conditions. Fluvial and marine flows, and sediment‐transport processes, impart a distinct river shape to each section, respectively. Nonetheless, a single river that extends from the uplands to the ocean requires that these distinct channel segments be connected; how that connection occurs is the focus of this study. The fluvial‐tidal transition channel is characterized by a rapid dissipation of incident tidal energy such that over a 15 km reach it declines to less than 1%, at 51 km inland. This rapid tidal energy dissipation favors the development of distinct breaks in along‐channel trends of many channel properties and riverbed sediment size. How these transition reaches can be expected to adjust in response to climate change and sea level rise remains largely unexplored. This knowledge gap is important because the transition zones along coastal plain rivers may become highly dynamic locations that affect the surrounding natural and built environments. Key Points: Reduced complexity analyses of tidal energy decay show that tidal waves lose 15%–17% per km of incident energy along the study reach Assessments of tidal energy decay and geomorphology show that tides impart sharp discontinuities in along‐channel geomorphic trends The fluvial‐tidal transition is ∼50 km inland and distinguished by a local high in cross‐section area and rapid decline in grain size